Humanitarian Crisis In The Israel Palestine Conflict During The 2025 Escalation - Adhi Munajar; Echa Eriza (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify the main factors contributing to the escalation of the conflict in 2025, examine its impact on the humanitarian conditions of civilians, and assess the extent to which the international community’s response has been able to address the crisis. Additionally, this research seeks to provide an overview of changes in patterns of violence, forms of resistance, and indicators of human rights violations that emerged throughout 2025. Thus, this study is expected to contribute academically to the understanding of contemporary conflicts and to the formulation of humanitarian-based recommendations.The method used is qualitative with a library research approach, analyzing literature from international organizational reports, journal articles, recent news coverage, human rights documents, and academic studies related to the Palestine Israel conflict. The data were analyzed descriptively and interpretatively to capture the conflict dynamics, global actors’ responses, and ongoing humanitarian conditions. This approach allows researchers to view the broader context without relying on field observations, which are difficult to conduct in active conflict zones. The results show that 2025 is marked by increased military attacks, limited access to humanitarian aid, and a growing number of internally displaced persons. Human rights violations have worsened, particularly among vulnerable groups such as children and women. The international community still faces major challenges in providing meaningful intervention due to differing geopolitical interests. In conclusion, the Palestine Israel conflict in 2025 demonstrates the urgent need for humanitarian-based approaches to conflict resolution and a stronger role from international institutions to protect civilians and ensure fair humanitarian access.